Analyzing surface temperature on street median parks in Malang’s hot-humid climate - Iyati, Wasiska; Hilmy, Ayu Nur Izzati; Fitriani, Rika Nur; Fidelista, Alya Nafisa; Wardoyo, Jono (ARTEKS : Jurnal Teknik Arsitektur, 2024)
In hot humid cities, the local microclimate can be moderated by the green open spaces. Differences in the characteristics of its hardscape and softscape elements can result in different thermal environmental conditions. As one of the green open spaces, the street median park can provide vegetation to reduce the air temperature of the region's microclimate. This paper analyzes the thermal characteristics of three street median parks in Malang, which are represent the green street medians in hot humid country of Indonesia. A thermal imaging camera was used to compare the hardscape and softscape surface temperature difference of the three parks. The thermal image results show that stone and paving materials have the highest surface temperatures. Stone as the higher surface temperature is shown in three green streets median. Coral stone has the highest surface temperature at 43.6 °C in Ijen and 42.03 °C in Veteran. Paving also has the highest surface temperature at 43.17 °C in Kunang-kunang. Grass or earth with trees has the lowest surface temperature at 28.53°C in Ijen, 27.93 °C in Kunang-kunang, and 29.17°C in Veteran Street median park. The difference in daytime surface temperature between hardscape and softscape reaches 12.86 °C in Veteran, 15.07 °C in Ijen, 15.24 °C in Kunang-kunang.